A Midterm Evaluation of Postoperative Platelet-Rich Plasma Injections on Arthroscopic Supraspinatus Repair: A Randomized Controlled Trial - Ebert, J.; Wang, A.; Smith, Anne; Nairn, R.; Breidahl, W.; Zheng, M.; Ackland, T. (Sage Publications, 2017)
© 2017, © 2017 The Author(s). Background: Platelet-rich plasma (PRP) has been applied as an adjunct to rotator cuff repair to improve tendon-bone healing and potentially reduce the incidence of subsequent tendon retears. Purpose: To investigate whether the midterm clinical and radiographic outcomes of arthroscopic supraspinatus repair are enhanced after repeated postoperative applications of PRP. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 60 patients (30 control; 30 PRP) were initially randomized to receive 2 ultrasound-guided injections of PRP to the tendon repair site at 7 and 14 days after double-row arthroscopic supraspinatus repair or not. A total of 55 patients (91.7%) underwent a clinical review and magnetic resonance imaging (MRI) at a mean of 3.5 years after surgery (range, 36-51 months). Patient-reported outcome measures (PROMs) included the Constant score, Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaire, Oxford Shoulder Score (OSS), and visual analog scale (VAS) for pain. Global rating of change (GRC) scale and patient satisfaction scores were evaluated. Structural integrity of the surgical repair was assessed via MRI using the Sugaya classification system. Results: At the midterm review, there was no difference between the groups for any of the PROMs. No differences between the groups were demonstrated for the subjective and range of motion subscales of the Constant score, although a significantly higher Constant strength subscale score was observed in the PRP group (3.3 points; 95% CI, 1.0-5.7; P =.006). There was no evidence for any group differences in MRI scores or retear rates, with 66.7% of PRP patients and 64.3% of control patients rated as Sugaya grade 1. Two control patients had symptomatic retears (both full thickness) within the first 16 weeks after surgery compared with 2 PRP patients, who suffered symptomatic retears (both partial thickness) between 16 weeks and a mean 3.5-year follow-up. Conclusion: Significant postoperative clinical improvements and high levels of patient satisfaction were observed in patients at the midterm review after supraspinatus repair. While pain-free, maximal abduction strength was greater in the midterm after PRP treatment, repeated applications of PRP delivered at 7 and 14 days after surgery provided no additional benefit to tendon integrity.